Evaluation of the ICA-NSF Water Quality Index in the micro-basins of the Río Dulce National Park as a tool in the comprehensive management of sustainable management, Livingston, Izabal, Guatemala, Central America - Robledo-Hernandez, José Adiel (2022)
The protected area called Río Dulce National Park is located in the northeastern Caribbean region of Guatemala. It is administered by the National Council of Protected Areas (CONAP) and governed by a master plan. However, it faces challenges every day, such as a) the increase in real estate development due to its scenic beauty, b) the population increase of the recognized communities within the various areas of the park, c) non-regularized discharges of ordinary and special wastewater. Given this incipient situation, it is necessary to evaluate the quality of the water in Río Dulce through internationally recognized methods; such is the case of the ICA-NSF Water Quality Index, with the aim of interpreting the results in a holistic manner and being able to discuss them in academic settings, not only locally, but also internationally. For this, twelve sampling stations were georeferenced at the source of the main tributaries along the Río Dulce National Park. After the collection of water samples and laboratory analysis of the parameters: fecal coliforms, hydrogen potential, biochemical oxygen demand, nitrates, total phosphorus, temperature, turbidity, total dissolved solids and dissolved oxygen, the ICA-NSF was estimated using the online calculator from the Water Research Center of the United States of America. In general, considering the quality of the water of the tributaries, the ICA-NSF varied between 71 and 90, which qualifies as good quality. The critical parameters in the decrease of the ICA-NSF in the various stations evaluated were the presence of fecal coliforms and total dissolved solids, which allows the generation of guidelines for the sustainable management of the Río Dulce National Park. It is concluded that the water of the Río Dulce is not suitable for human consumption directly, requiring a purification process.